A multidimensional analysis of temporomandibular joint and ankle joint erosion in inflammatory arthritis - Andreev, Darja; Porschitz, Pauline; Weidner, Daniela; Song, Rui; Weider, Matthias; Schett, Georg; Gölz, Lina; Bozec, Aline (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) and other inflammatory arthritis are systemic diseases that primarily affect the joints, characterized by synovial inflammation and progressive cartilage and bone degradation. The temporomandibular joint (TMJ) is reported to be involved in over 50% of RA cases, often leading to severe jaw pain and compromised oral function. Despite its prevalence, TMJ involvement is often underestimated, and its cellular and molecular mechanisms remain poorly understood. Due to the unique biological and functional properties of the TMJ, inflammatory pathways observed in other joints such as the well-studied ankle joint may not directly apply to the TMJ. This study aimed to establish a reliable inflammatory arthritis model for investigating TMJ-specific pathomechanisms. The human TNF-α transgenic (hTNFtg) mouse model effectively replicated TMJ pathology seen in arthritic patients, including increased synovial inflammation (p=0.0024) and severe bone loss (p=0.009) as compared to control mice assessed by micro-computed tomography and histomorphometry. These changes were driven by increased osteoclast numbers (p=0.0331) and upregulation of genes associated with bone resorption such as Acp5 (p=0.0003) and Ctsk (p=0.0025). Notably, we observed that the TMJ displays a unique pattern of immune cell infiltration and pro-inflammatory cytokine expression compared to the ankle joint, particularly with respect to T cell recruitment. These findings were further supported by bulk RNA sequencing, which revealed overall increased inflammation in both the ankle joint and TMJ of hTNFtg mice compared to the control group. Interestingly, while the expression of immune cell and pro-inflammatory cytokine-related gene sets was higher in the ankle joint, the TMJ showed increased expression of genes associated with energy consumption and bone resorption-related enzymes. These findings highlight the TMJ as a distinct anatomical site with heightened susceptibility to arthritis-related damage and emphasize the need for greater awareness and targeted research to improve disease management for affected individuals.